Bilateral Severe Sterile Inflammation with Hypopyon after Simultaneous Intravitreal Triamcinolone Acetonide and Aflibercept Injection in a Patient with Bilateral Marked Rubeosis Associated with Ocular Ischemic Syndrome - Ceren Durmaz Engin; Ziya Ayhan; Süleyman Men; Aylin Yaman; A. Osman Saatci (Case Reports in Ophthalmological Medicine)
We report the clinical course of a diabetic patient with bilateral cataract and rubeosis in association with ocular ischemic syndrome and initially treated him with simultaneous intravitreal 2 mg aflibercept and 2 mg triamcinolone acetonide injection at the same setting prior to planned cataract surgery and further photocoagulation. However, sterile anterior segment inflammation characterized by hypopyon occurred four days apart in OU. Right eye developed the sterile inflammation at the third postinjection day and the left eye developed the sterile inflammation at the seventh postinjection day (two days after the uneventful cataract surgery with intraocular lens implantation) without any pain or significant redness. Vitreous biopsy taken during the right phacovitrectomy was negative for any microbial contamination. Both eyes were treated successfully with intensive topical prednisolone acetate with a relatively good visual outcome. It is likely that underlying ocular ischemic syndrome might have facilitated the formation of sterile inflammation as blood-aqueous barrier disruption and flare have already been present.